Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Memilih Produk Asuransi Syariah - Ami Radianti; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
This study focuses on consumer behavior, sharia insurance, and the factors that influence consumer behavior in sharia insurance. The research objectives are (1) to determine consumer behavior, (2) to determine what factors influence consumer behavior factors, (3) to determine sharia insurance. The method used in this research is the literature study method, which is a method that uses a series of research activities by collecting library data, reading and recording important things, such as we can take this research material through journals, articles, trusted websites, and books that we got. The results obtained are to understand what Islamic insurance is, understand consumer behavior, consumer behavior models, and find out what factors influence consumer behavior in Islamic insurance. Keywords: Factors, Influence, Consumer Behavior, Sharia Insurance